Factors associated with health-related quality of life in patients with chronic liver disease in Korea: a cross-sectional study - Gum Mo Jung; Jihyon Pahn (Journal of Korean Biological Nursing Science, 2026)
Purpose: This study aimed to identify factors associated with health-related quality of life (HRQoL) in patients with chronic liver disease and to provide foundational data for developing intervention programs.Methods: This cross-sectional study included 166 patients recruited from a general hospital in Jeonju, South Korea. Data were collected using structured questionnaires assessing depression, uncertainty in illness, and subjective health status and were analyzed using descriptive statistics, the independent t-test, one-way analysis of variance, Pearson correlation coefficients, and multiple regression analysis using SPSS version 23 program.Results: The mean HRQoL score was 3.19 ± 0.54 (range 1~5). Depression, uncertainty in illness, subjective health status, and education level were significant factors associated with HRQoL. Higher depressive symptom scores (β = -.24, p = .002) and greater uncertainty in illness (β = -.15, p = .044) were associated with lower HRQoL, whereas better subjective health status (β = .34, p < .001) and a higher education level were associated with higher HRQoL.Conclusion: These findings may inform intervention programs to improve HRQoL in patients with chronic liver disease by addressing depressive symptoms, uncertainty in illness, subjective health status, and educational needs.